AIbō : Design and Evaluation of an Ontology-Guided AI Sales Assistant for Partner Incentive Programs - Šmíd, Soňa; Černý, Jan; Škrabálek, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
AIbō is a conversational AI assistant designed to support Adastra's sales and alliance teams in navigating complex partner incentive programs. It is powered by a Retrieval Augmented Generation (RAG) pipeline grounded in a vendor-agnostic ontology and connected to an OpenAI language model through a FastAPI backend and a Supabase PostgreSQL vector database. The objective of AIbō is to reduce manual administrative effort, improve the accuracy and speed of incentive discovery, and support revenue acceleration through more effective use of partner funding. This MBA project presents the design, implementation, and evaluation of an AIbō prototype built on a Lovable frontend, FastAPI backend, and Supabase database, with development support provided by Cursor IDE and an intended migration path to Agate, Adastra's enterprise GenAI platform. The prototype achieved measurable improvements in accuracy, citation reliability, and correct display of visibility tags (internal and external) in citations, validating ontology-guided retrieval as an effective approach for enterprise assistants. A key finding of the pilot was that ontology-backed responses reached 77.6% accuracy and 100% citation reliability, outperforming non-ontology queries by 34.3 percentage points. Web search functionality and partner portal integration were intentionally disabled during the pilot to focus on the robustness of RAG-only retrieval, ensuring that performance reflected the system's reasoning supported by low-temperature model settings aimed at factual consistency. In future iterations, AIbō will evolve toward agentic functionality, capable not only of retrieving information but also of proactively managing knowledge through change detection, escalation, and integration with partner portal APIs. The project contributes to applied research by demonstrating how ontology and RAG can be combined through vibe coding to create conversational systems that deliver tangible business value.
Vedoucí práce: Jan Černý
Závěrečná práce - Institut celoživotního vzdělávání (MBA)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet